engembangan E-LKPD Berbasis STEM dengan Konteks Polusi Udara Samarinda untuk Meningkatkan Literasi Lingkungan dan Keterampilan Berpikir Kritis Murid SMP - Nurlaila; Elsje Theodora Maasawet; Akhmad; Herliani; Masitah; Lambang Subagiyo (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop STEM-based E-LKPD to improve environmental literacy and critical thinking skills of eighth grade junior high school students on respiratory system content, with a context of solving air pollution problems caused by waste burning in Samarinda. The background of this study is the low ability of students to relate scientific concepts to local environmental issues and their weak critical thinking and environmental literacy skills in biology learning. The research method used was Research and Development (R&D) with Thiagarajan's 4D (Define, Design, Develop, Disseminate) model. Experts validated the product in subject matter, media, and language, and its practicality was tested through a student response questionnaire. The effectiveness test was conducted using a pretest-posttest control group quasi-experimental design in four public junior high schools in Samarinda (SMPN 1, 7, 19, and 26). The expert validation results showed that the product was highly valid with an average percentage of 91.66%. The practicality test resulted in a very practical category at the dissemination stage (average score of 3.5–3.7). The effectiveness test proved that the experimental group using STEM-based E-LKPD experienced a significantly higher increase in environmental literacy and critical thinking skills compared to the control group, with a medium-high N-Gain category (0.4–0.8) and statistical significance of p < 0.05. These findings suggest that anchoring STEM learning in the tangible, local issue of air pollution in Samarinda effectively bridges the gap between abstract scientific concepts and real-world application, thereby fostering deeper environmental literacy and critical thinking. The study concludes that the developed STEM-based E-LKPD is a feasible, practical, and innovative medium aligned with the Merdeka Curriculum and the Sustainable Development Goals.